(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: Describe the reality of physical activity and personal factors and family related to physical activity of Tay Bac University students in the school year 2020-2021. Methods: A cross-sectional descriptive study with analysis was conducted on 832 students at Tay Bac university. Research results: The rate of adequate physical activity was 54,4%, the rate of lack of physical activity was 45,6%. In which, 24,6% of students have active physical activity, 29,8% have moderate physical activity and 45,6% have low physical activity. The rate of lack of physical activity in women (50,5% of the total number of women) is higher than men (38,1% of the total number of men). The correlation analysis showed that there are factors such as gender (p<0,001), ethnicity (p <0,001), student’s living area (p <0,001), school year (p <0,001) and some factors such as family and friends are related to students’ physical activity level. Conclusion: The rate of lack of mental activity of Tay Bac University students is 45,6%, full physical activity is 54,4%. Factors related to the level of physical activity recorded were gender, ethnicity, student’s living area, school year, support of family and friends.